Combination Therapy of Albumin-Bound Paclitaxel and Carboplatin as First Line Therapy in a Patient with Ovarian Cancer. (3rd April 2014) - Srinivasan, K. N; Rauthan, Amit; Gopal, R.
Abstract : Background . Ovarian cancer is the ninth most common cancer among women and causes more deaths than any other type of female reproductive cancer. Albumin-bound paclitaxel is known to increase intratumoral concentration of the paclitaxel by a receptor-mediated transport process across the endothelial cell wall, thereby breaching the blood/tumor interface. We present below three cases in which nab-paclitaxel based chemotherapy has been used in different settings for patients with ovarian cancer. Case Presentation . In the first case nab-paclitaxel was used along with carboplatin in adjuvant setting, in the second case, nab-paclitaxel was used along with carboplatin and bevacizumab as second line chemotherapy in a relapsed ovarian cancer case, and the third case delineates the use of nab-paclitaxel along with cisplatin as third line chemotherapy. Conclusion . In all the three scenarios, patients tolerated the chemotherapy well, as well as responding well to nab-paclitaxel based chemotherapy. The patients are currently on long-term follow-up and have been having an uneventful postchemotherapy.